Socially responsible training of the future leaders the socially responsible formation of the future enterprise leaders : analysis of the perception of one of the interested parties Spain – Argentina - Corral, Silvia Luján (2017)
Fil: Corral, Silvia Luján. Universidad Nacional del Centro de la Provincia de Buenos Aires. Facultad de Ciencias Económicas; Argentina.